Posttraumatic stress symptom clusters differentially predict late positive potential to cocaine imagery cues in trauma-exposed adults with cocaine use disorder. (1st October 2021) - Webber, Heather E.; Kessler, Danielle A.; Lathan, Emma C.; Wardle, Margaret C.; Green, Charles E.; Schmitz, Joy M.; Lane, Scott D.; Vujanovic, Anka A.
Highlights: PTSD symptoms are related to increased cocaine cue reactivity. Relations of PTSD to late positive potential to cocaine imagery cues were evaluated. PTSD cognition/mood symptoms were associated with increased cocaine cue reactivity. PTSD arousal/reactivity was associated with decreased response to cocaine cues. Abstract: Background: While studies have investigated the effects of posttraumatic stress disorder (PTSD) symptoms on substance use, information on these associations in the context of drug cue reactivity is lacking, which can provide meaningful information about risk for relapse. The current study assessed the associations between PTSD symptom clusters and reactivity to cues in trauma-exposed adults with cocaine use disorder. Methods: We recorded electroencephalogram on 52 trauma-exposed participants ( M age = 51.3; SD = 7.0; 15.4 % women) diagnosed with cocaine use disorder while they viewed pleasant (i.e., erotic, romantic, sweet foods), unpleasant (i.e., mutilations, violence, accidents), neutral, and cocaine-related images. Reactivity was measured with the late positive potential (LPP), an indicator of motivational relevance. It was hypothesized that individuals with greater PTSD avoidance and negative alterations in cognition and mood (NACM) symptoms, as determined by the PTSD Checklist for DSM-5 (PCL-5), would have higher LPPs to cocaine-related images, indicating greater cue reactivity. Results: Linear mixed modeling indicated that higher NACM symptomatology was associated with higher LPPs to cocaine cues and higher arousal/reactivity was associated with lower LPPs to cocaine cues. Conclusions: These results highlight the potential clinical utility of the LPP in assessing drug cue reactivity in trauma-exposed adults with substance use disorder.